Geobotanical characterisation of the Trifolion squamosi nom. corr. alliance (class. Juncetea maritimi) in Catalonia and the Western Mediterranean - Mercadal i Corominas, Gabriel (Hacquetia, 2020)
We present a summary of part of the phytogeographic results described in the author’s PhD thesis. In this case, we characterise and validate several syntaxa of subsaline meadows in the Trifolion squamosi nom. corr. alliance (class. Juncetea maritimi) in Catalonia (incl. NE Spain and SE France) and in other regions of the Western Mediterranean (N Algeria, Languedoc and Provence). In total, we study six syntaxa in geobotanical terms, based on synthetic tables and factor analyses of correspondence published previously in the thesis: one alliance (Trifolion squamosi), two associations and three subassociations (Agropyro-Trifolietum subass. typicum, subass. festucetosum comb. nova, subass. brachypodietosum nova; Festucetum arundinaceae).